Effect of Cooking and Processing on Quantitation of Soybean Proteins - Akiyama, Haruyo; Masaoka, Tomoka; Imura, Kaori; Iseki, Naomi; Osawa, Nobuhiko; Watanabe, Hiroko; Ueda, Sumiko; Akaboshi, Chie (Food Hygiene and Safety Science (Shokuhin Eiseigaku Zasshi), 2021)
We examined the effects of cooking and processing on the quantitation of soy protein in various soy-based foods. For the phosphate-buffered saline (PBS) extraction, the total protein content was measured by bicinchoninic acid assay, and the buffer extraction containing sodium dodecyl sulfate (SDS) and 2-mercaptoethanol (ME) was measured by the 2-D Quant Kit, and SDS-polyacrylamide gel electrophoresis analysis (SDS-PAGE) of each extraction was performed. Furthermore, measurements were performed by various ELISAs. During the tofu cooking process, the protein concentrations of soaked soybeans and Seigo (soybean homogenized with water) fluctuated- the change in protein solubility due to the amount of water during sample homogenization was considered to be a factor. It was thought that the decrease in protein concentration due to heating of Seigo during soymilk production was considered to indicate thermal denaturation of the protein, and that SDS and ME extraction in tofu may affect the measurement system. In cooking excluding roasted beans, proteins with a mass of 50 kDa or above and around 20 kDa were denatured, and in twice-fried tofu, proteins around 40 kDa were denatured, but the protein concentration excluding boiled soybeans did not decreased. Furthermore, the protein concentration from roasted beans, yuba, roasted okara and fried tofu increased with the cooking time, suggesting that the denaturation temperature of the protein shifted to a high temperature as the water content decreased. Both of the two types of ELISAs that comply with the official labeling system of foods containing allergenic substances were useful for detecting soybean protein by detecting proteins and peptides in processed soybean products, fermented foods excluding natto, and health foods.